DJ-1 Deficiency Protects against Sepsis-Induced Myocardial Depression - James N. Tsoporis; Hajera Amatullah; Sahil Gupta; Shehla Izhar; Amin M. Ektesabi; Chirag M. Vaswani; Jean-Francois Desjardins; Golam Kabir; Ana Paula Teixera Monteiro; Amir K. Varkouhi; Nikolaos Kavantzas; Vasileios Salpeas; et al. (MDPI AG, 2023)
Oxidative stress is considered one of the early underlying contributors of sepsis-induced myocardial depression. DJ-1, also known as PARK7, has a well-established role as an antioxidant. We have previously shown, in a clinically relevant model of polymicrobial sepsis, DJ-1 deficiency improved survival and bacterial clearance by decreasing ROS production. In the present study, we investigated the role of DJ-1 in sepsis-induced myocardial depression. Here we compared wildtype (WT) with DJ-1 deficient mice at 24 and 48 h after cecal ligation and puncture (CLP). In WT mice, DJ-1 was increased in the myocardium post-CLP. DJ-1 deficient mice, despite enhanced inflammatory and oxidative responses, had an attenuated hypertrophic phenotype, less apoptosis, improved mitochondrial function, and autophagy, that was associated with preservation of myocardial function and improved survival compared to WT mice post-CLP. Collectively, these results identify DJ-1 as a regulator of myocardial function and as such, makes it an attractive therapeutic target in the treatment of early sepsis-induced myocardial depression.